Steel square use of the scales, roof framing, illustrative problems, other uses - Townsend, Gilbert (American Technical Pub, 1947)
Steel Square is a classic textbook that provides fundamental knowledge about the steel square and its use on construction projects. The textbook includes information on laying out rafters, braces, joists, and partitions.